The Impact of Government Stability on Libyan International Reserves: An Econometrics Study Using the ARDL Model - امبيه د.عبدالحكيم (Journal of Pure & Applied Sciences, 2021)
This study aims to measure the impact of government stability on Libyan international reserves during the period (1984-2018), using the Autoregressive Distributed Lagged Model (ARDL). The study founds the short and long term relationship between the variables. Also, the results of the study indicate that the Lagged international reserves variable has the greatest ability to explain the changes on the international reserves, and the government stability variable is positively effects on the international reserves, which, meaning that the improvement and stability of government in Libya will lead to an improvement the international reserves.